تأثير قيم الـ (pH) ودرجة الحرارة على أكسدة شوارد السولفيد بالكلور الموجودة في مياه الصودا المستهلكة في وحدة الميروكس في شركة مصفاة بانياس - أبظلي هشام; غفر محمد; عبد الله عبد الرزاق (Latakia University Journal -Basic Sciences Series, 2013)
تحتوي مياه الصودا المستهلكة الناتجة عن وحدة الميروكس في شركة مصفاة بانياس على كمية كبيرة من شوارد السولفيد التي تتحول في وسط حمضي إلى غاز كبريت الهيدروجين الذي له الأثر البالغ على صحة الإنسان وعلى البيئة, لذلك فإن الهدف الرئيسي للبحث هو تخفيض كمية شوارد السولفيد من خلال أكسدتها بالكلور. أخذت كمية من مياه الصودا المستهلكة في وحدة الميروكس, وأجريت الدراسة على(100 غرام ) من المياه في كل تجربة, وأكسدت العينات بالكلور(بشكل هيبوكلوريت الصوديوم التجاري) بكميات مختلفة من هيبوكلوريت الصوديوم, وقيست كمية الكبريت, على شكل شوارد السولفيد, في كل تجربة, وبلغت نسبة استرداد الكبريت, بشكل شوارد السولفيد, 95.419% عند درجة الحرارة (-5 C°), بينما بلغ وزن الكبريت الغروي على شكل راسب(0.125 غرام). وبقيت كمية الكبريت على شكل الكبريتات ثابتة في كل التجارب. Contain soda water consumed resulting from unit Almirox in oil refinery in Banias on the large amount of ions sulphide which turn in the miduim of an acid to a gas hydrogen sulphide which has a deep impact on human health so the main thrust of this research is to reduce the amount of ions sulphide throughoxidized chlorine . Given the amount of soda water consumed per unit Almirox, and the study was on the (100 grams) of water in each experiment and Oxidation samples chlorine (a sodium hypochlorite commercial) different amounts of sodium hypochlorite and has measured the amount of ions sulphide in each experiment, and the amount of ions sulphide remaining, 95.419% at ambient temperatures (-5 ° C), a lower value, while the weight of colloidal sulfur sludge output (0.125 grams), which is the highest value and the amount of sulfates remain constant in all tests.